Effect of muscle selection for botulinum neurotoxin treatment on spasticity in patients with post-stroke elbow flexor muscle over-activity: an observational prospective study. (2nd January 2022) - Şengül, İlker; Aşkın, Ayhan; Tosun, Aliye
Abstract: Purpose/Aim: To investigate the effect of muscle selection for botulinum neurotoxin A (BoNT-A) treatment on spasticity in patients with post-stroke elbow flexor muscle over-activity. Materials and Methods: Chronic stroke patients with a deforming spastic paresis in the upper limb (elbow flexion with forearm pronation) who were injected BoNT-A into at least one of elbow flexor muscles (brachialis, brachioradialis, and biceps brachii) were included in this prospective observational study. The main outcome measure was spasticity angle by Tardieu Scale recorded at pre-treatment and week 4 after treatment. Results: Three muscle selection groups with sufficient sample size for statistical analysis were able to be created; brachialis ( n  = 14), biceps brachii ( n  = 21), and brachialis plus brachioradialis ( n  = 11). Although there was a significant improvement in spasticity angle within all groups over time ( p  < 0.05), the change in spasticity angle was not different between the groups ( p  > 0.05 for each pairwise comparison). However, the magnitude of the change in spasticity angle was larger in the groups in which brachialis was preferred. Conclusions: In stroke patients with a spontaneous spastic posture of elbow flexion and forearm pronation, targeting brachialis for BoNT-A injection seems more effective in reducing the severity of spasticity. Clinical trial registration no: NCT04036981